Application of the MOORA and TOPSIS Methods in the Evaluation of Tax Administration Strategies based on Taxpayer Identification Numbers (NPWP), Services, Sanctions, and Taxpayer Understanding - Sri Umiatun Andayani; Dyah Kusumawati; Mustagfirin Mustagfirin (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
Taxpayer compliance is a crucial factor in optimizing state revenue through the taxation sector. Although the number of taxpayers in Indonesia continues to increase, the level of voluntary compliance is still relatively low, so an effective tax administration strategy is needed to improve it. This study aims to analyze the influence of the benefits of Taxpayer Identification Number (NPWP), service quality, administrative sanctions, and tax understanding on taxpayer compliance, and determine the most optimal tax administration strategy using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. This approach was chosen because it is able to provide objective and measurable analysis results based on complex criteria. The MOORA method is used to normalize and weight each criterion, while TOPSIS is used to determine the most ideal strategic solution. The results show that the strategy of increasing tax socialization and sending warning letters to taxpayers who violate is the most effective step to increase taxpayer compliance. Sensitivity analysis shows that the MOORA method has a better level of stability of results with an average sensitivity value of -1.61%, compared to TOPSIS at -7.96%. Thus, the MOORA method is considered more appropriate for use in the context of evaluating tax administration strategies. This research significantly contributes to the development of data-driven tax policies and enriches the literature on the application of multicriteria decision-making methods in tax administration in Indonesia.